Regulated drug bioanalysis for human pharmacokinetic studies and therapeutic drug management. (August 2012) - Huang, Yong; Shi, Robert; Gee, Winnie; Bonderud, Richard
Regulated drug bioanalysis (i.e., determination of drug concentrations in biological matrices for regulated studies) usually refers to animal toxicokinetics, bioavailability/bioequivalence and clinical pharmacokinetic studies. However, there is another important regulated drug bioanalysis – therapeutic drug management (TDM). In the USA, TDM is regulated by Clinical Laboratory Improvement Amendments. In this article, we review and compare human pharmacokinetic sample analysis and TDM sample analysis. The US FDA/Bioanalytical Method Validation Guidance and the American Association for Clinical Chemistry/TDM Roundtable Recommended Generic Assay Validation Guidance are also compared. Some regulated drug bioanalysis issues, such as terminology, validation concepts and acceptance criteria, are discussed. Fostering interaction between bioanalysts from pharmaceutical science and clinical chemistry and reducing the regulatory gaps between different agencies for drug bioanalysis is our objective.